Integritas Aparatur dan Etika Birokrasi sebagai Pilar Kualitas Pelayanan Publik: Studi Kasus Kelurahan 27 Ilir, Palembang - Permata Sari, Intan Dwi; Cahya Putri, Naila; Berliana Safitri, Aisyah; Riana, Ica; Hartanti, Febbry; Wulan Agustien, Zahfarina; Mashary, Try; Sahadewa, Ariel; Aini, Syarifah; Keril, Radia; Adelia Suryani, Riza (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
Quality public service is a manifestation of the government’s responsibility to fulfill community needs, particularly at the village level as the frontline of public service delivery. This study aims to examine the implementation of bureaucratic integrity and ethics in improving the quality of public services at the 27 Ilir Subdistrict Office, Ilir Barat II District, Palembang City. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, documentation study, and literature analysis. The informants consisted of subdistrict officials and community members as service users. The findings indicate that the implementation of integrity and bureaucratic ethics at the 27 Ilir Subdistrict Office has been carried out effectively, as reflected in honest, disciplined, fair, and non-discriminatory service practices. Policies emphasizing clean, transparent, and levy-free services, along with the application of digital-based services, have contributed to improving service quality and public satisfaction. However, technical constraints such as internet network disruptions remain a challenge in online service delivery. Overall, this study concludes that bureaucratic integrity and ethics play a crucial role in enhancing public service quality and strengthening public trust in subdistrict officials, and therefore should be continuously reinforced and developed in a sustainable manner.